The Role of Transformational Leadership Style on Islamic Management - Ibrahim Fahad Sulaiman; Ahmed Abdul Malik; Zainab Masud Abdul Raheem (Kirana Publisher (KNPub), 2024)
The process of engaging in organizations to transform its entities may request for more affordable leadership style. This study focuses on the impact of transformational leadership style on Islamic management in higher institution of learning. The components of transformational leadership style namely, idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration were utilized to examine the validity on the two components of Islamic management namely, forgiveness and sincerity. Stratified sampling was used to sample 80 respondents from Faculty of Leadership and Management USIM. Bass & Avolio (1993) questionnaire was adopted and adapted for the study. Correlation analysis and Multiple regression analysis were used to examine the relationship between transformational leadership style and Islamic management components. The results show that all transformational leadership style component is statistically significant on Islamic management which account for 69% of the variance explain by the individualized consideration, idealized influence, intellectual stimulation, and inspirational motivation.